2020
DOI: 10.1155/2020/6681352
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activity of Eriodictyol: The Major Natural Polyphenolic Flavanone

Abstract: Eriodictyol is a flavonoid that belongs to a subclass of flavanones and is widespread in citrus fruits, vegetables, and medicinally important plants. Eriodictyol has been anticipated to explain the method of its activity via multiple cellular signaling cascades. Eriodictyol is an effective natural drug source to maintain higher health standards due to its excellent therapeutic roles in neuroprotection, cardioprotective activity, hepatoprotective activity, antidiabetes and obesity, and skin protection and havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Eriodictyol is a hydroxylated flavonoid compound widely present in citrus fruits, vegetables, and many medicinal plants [ 1 ]. This plant-based natural product has antioxidative, anti-inflammatory and neuroprotective effects, and can thus be potentially used in pharmaceutical, nutraceutical, or food industries [ 1 3 ]. At present, the main way of obtaining eriodictyol is via extraction from plants or chemical synthesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eriodictyol is a hydroxylated flavonoid compound widely present in citrus fruits, vegetables, and many medicinal plants [ 1 ]. This plant-based natural product has antioxidative, anti-inflammatory and neuroprotective effects, and can thus be potentially used in pharmaceutical, nutraceutical, or food industries [ 1 3 ]. At present, the main way of obtaining eriodictyol is via extraction from plants or chemical synthesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural molecules isolated from plants may be promising alternatives to synthetic chemicals for the management of periodontal disease [ 20 , 21 ]. Eriodictyol { Figure 1 ; [(S)-2-(3,4-dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one]} is a flavonoid belonging to the flavanone subclass and is mainly found in the traditional medicinal plant yerba santa ( Eriodictyon californicum ) as well as in citrus fruits and vegetables [ 22 , 23 ]. Studies carried out over the past decade have shown that eriodictyol exibits a number of therapeutic properties, including antioxidant and anti-inflammatory effects [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eriodictyol { Figure 1 ; [(S)-2-(3,4-dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one]} is a flavonoid belonging to the flavanone subclass and is mainly found in the traditional medicinal plant yerba santa ( Eriodictyon californicum ) as well as in citrus fruits and vegetables [ 22 , 23 ]. Studies carried out over the past decade have shown that eriodictyol exibits a number of therapeutic properties, including antioxidant and anti-inflammatory effects [ 22 , 23 ]. The therapeutic properties of eriodictyol appear to depend on its capacity to modulate several cell signaling pathways [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eriodictyol (ED) [IUPAC name (2S)-2-(3,4-dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one], is a avonoid in the avanones subclass abundantly found in various medicinal plants, citrus fruits, and vegetables (Islam et al 2020). ED has multiple therapeutic effects such as anti-oxidant, anti-cancer, antiammatory, and neuro-protective bioactivity (Clavin et al 2007; Deng et al 2020;Islam et al 2020;Lv et al 2021). Such numerous pharmacological and biological roles of ED have attracted much research interest for increasing titer and quality (Marin et al 2017).…”
Section: Introductionmentioning
confidence: 99%